Analysis Of Aplications Mobile GPS Tracker In Public Transportation - Candra B; Ariani F (Bandar Lampung University (UBL), 2017)
Vehicles in Bandar Lampung its rapid growth, this time a lot of private vehicles filled the streets in the city of Bandar Lampung, this situation would further lead to congestion, one of the ways the government to address congestion in the city of Bandar Lampung is to facilitatepublic transport for the public, but as far as public transportation in the city of Bandar Lampung can not give comfort to the people. Viewed from a phenomenon that exists today some firms have sought to exploit the situation, but the company is only concerned with his or her business or for-profit are not concerned with the public interest, it can not help the government to deal with the public, such as the case of his company Gojek, Uber, and Grabthey drove his passengers did not use mass transportation, the results obtained less than the maximum they can not handle the existing congestion. We make onlinesystem gps tracker which utilizestechnology of theGlobalPositioning System available today, can provide precise and accurate information, the public is more in make it easy and get better service. GPS is a satellitebased navigation system developed by the US Department of Defense (US Department of Defense DoD) in early 1970. GPS was originally developed for military purposes in the United States, then in the 1980s opened GPS access also for civilian purposes so that the current GPS can be used both for military and civilian users. At that time in 1973 there are 31 GPS satellites that orbit the Earth (source: http://www.gps.gov,Official US Government information about the Global Positioning System andrelated topics). These satellites transmit the coordinates to a receiver on the ground. The GPS system can monitor and determine the location of an object that wants to be known almost anywhere in the surface of the earth. GPS will capture the satellite signal from the surface of the earth to be translated into a coordinate point. The coordinates of the point we can integrate digital maps to findthe position of an object.